ANALISIS PUISI HERI ISNAINI “PRANGKO” DENGAN PENDEKATAN SEMIOTIKA - Puji Nurul Amalia Putri; Tiana Puspitasari; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Fiction in literary works in the form of essays or experiences that can be devoted to an article using interesting language, not standardized. Poetry, one of the forms of fiction, contains implicit meaning. Poetry can motivate writing lovers, especially readers who are interested in knowing the meaning of the implicit meaning of a poem through analysis. Based on the previous explanation, the author was interested in conducting a study, namely analyzing the poem by Heri Isnaini entitled "Stamps" using the semiotic approach. This study aims to (1) analyze the poem semiotically, (2) describe the results of poetry analysis entitled "Stamps" ( 3) describe the main issues on the theme of the poem. The method of description is the method used in this study, namely telling or describing the contents of the poem analyzed. Stamp poetry is analyzed and discussed semiotically to find out about the meaning and signs of the language so that the hidden meaning of the poem can be clearly revealed. The results show that the poem means something textually, stamps that are likened to humans. Therefore, the image of the stamp can be likened to a pair of figures that are likened to a stamp, where the stamp remains loyal to the worn envelope and has even turned yellow. Yellowing in the poem can be described by someone who is no longer worthy an old and unattractive figure.